2003
DOI: 10.1097/01.ta.0000038550.11890.a5
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Correlation of Temporal Bone Fractures and Spiral Computed Tomographic Scan: A Prospective and Consecutive Study at a Level I Trauma Center

Abstract: TBFs are common injuries in patients with head trauma. More than one third of these fractures may be missed by clinical diagnosis alone. Although the clinical importance of the missed TBF is debatable, 12% of our patients developed complications. Therefore, to rule out these lesions, routine cranial helical CT scan should be recommended in all patients presenting with head trauma, independent of clinical findings and GCS score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…[2][3][4][5][6] Males are three to four times more prone to trauma than females. 1,7 Bilateral temporal bone fractures are sustained by 8 to 29% of patients. 1,[7][8][9] to 1,800 lb.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Males are three to four times more prone to trauma than females. 1,7 Bilateral temporal bone fractures are sustained by 8 to 29% of patients. 1,[7][8][9] to 1,800 lb.…”
Section: Epidemiologymentioning
confidence: 99%
“…1,7 Bilateral temporal bone fractures are sustained by 8 to 29% of patients. 1,[7][8][9] to 1,800 lb. 10,11 Fractures tend to take the path of least resistance in the bone and follow native foramina within the temporal bone.…”
Section: Epidemiologymentioning
confidence: 99%
“…The limited literature concerning tympanic plate fracture (TPF) suggests that these types of fractures are uncommon. 4,10,11,16 Most literature on direct and indirect CT findings of temporal bone trauma was published in the pre-/early multidetector CT era 1,3,7,17,18 or was based solely on non-high-resolution CT (HRCT) imaging, 19 ;…”
mentioning
confidence: 99%
“…TBFs account for 18% to 22% of all skull fractures in general7 and 18% to 40% of all head injuries involving the cranial base 1. Exadaktylos et al reported a TBF incidence of 10.9% in a prospective series of 350 patients with head trauma at a level I trauma center 8. Separately, Elahi et al reported a 3.69% incidence of CSI in a cohort of 3,356 Canadian patients with craniomaxillofacial fractures from 1994 to 2003, although in that study the fractures were categorized into skull and upper, middle, and lower facial thirds; TBFs were not specifically analyzed 9…”
Section: Introductionmentioning
confidence: 99%